DYNAMICS OF Acartia lilljeborgii GIESBRECHT, 1889 IN A HEAVILY INDUSTRIALIZED TROPICAL ESTUARY - Mugrabe, Glenda; Melo, Pedro Augusto de Castro Mendes; Neto, Fernando de Figueiredo Porto; Silva, Andrea Pinto; Neumann-Leitão, Sigrid (Revista Nordestina de Zoologia, 2013)
Studies about the dynamics of the Copepoda Acartia lilljeborgii Giesbrecht, 1889 were carried out at Suape, Pernambuco, Brazil, in order to use this species as environmental quality indicator, after major changes that occurred throughout the development of this area after industrial enterprises. Suape Bay and the Tatuoca River estuary were studied, from May/2009 to November/2010. Sampling was carried out in two stations (S1 and S2), during spring and neap tides, on low and high tides. Plankton collections were made with a plankton net 300 µm mesh size. Considering the total density of zooplanktonic community, Copepoda represented 78%, and Acartia lilljeborgii contributed with 48%, occurring in all samples. The density ranged from a minimum of 1.4 ind.m-3 (S2, April/2010, low tide, spring tide) to a maximum of 646.8 ind.m-3 (S1, March 2010, high tide, spring tide) with general average of 73.2±166.6 ind.m-3. S2 and the low tides showed lower densities and biomasses. Despite of all impacts on Suape Bay, Acartia lilljeborgii presented high resilience, maintaining as the dominant species in the last decades.